From carotene-rich waste-to-food: Extraction, food applications, challenges and opportunities - Tomas, Merve; Kamiloglu, Senem; Nemli, Elifsu; Ozdal, Tugba; Haque, Shafiul; Apak, Resat; Capanoglu, Esra (Elsevier BV, 2025)
Background: Food waste products of industrial processing pose environmental and economic problems. Although there are existing studies in the current literature regarding the evaluation of carotene-rich waste, there is a need for innovative and up-to-date information on the valorization of these wastes. Scope and approach: This article aims to provide an extensive approach to food waste valorization, extraction of carotenoids from waste including potential sources of functional food ingredients, food applications, and life cycle assessment in terms of carotene-rich wastes. Key findings and conclusions: Recovery of carotene from food waste is an important strategic aim in terms of a sustainable agriculture system and the development of functional foods and natural food colorants. In this sense, various green extraction techniques are used for high yields and the best quality carotenoids. Combining green extraction methods including pulsed electric field (PEF) and ultrasound-assisted extraction (UAE) or pressurized liquid extraction (PLE) and supercritical fluid extraction (SFE) may be an efficient approach. However, research on the extended applications of these carotenoid-rich extracts is scarce, so future studies should focus on their potential use in various food materials. Therefore, further studies are required to cover the current gaps relating to the upcoming valorization of carotenes.
Keywords: carotene; Sustainability; waste; Extraction; Valorization; Food application